Peran Perempuan Karir Dalam Pola Asuh Anak Di Era Digital Di Perum Villa Ajung Bumi Asri - Okta Viana Dwi Anisa; Nandina Putri Salsabilla; Muhammad Ridwan Arif; Alfisyah Nurhayati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
In today's digital era, technology and information are developing rapidly. This technological development has an influence in the educational and social fields. Thus, career women have a heavier burden. On the one hand, he must be responsible for his household affairs, on the other hand, he must also be responsible for his office work. This is often very vulnerable to causing problems. This research method uses a descriptive qualitative research method because this research tends to analyze and describe the perspective of the target subject, namely career mothers. To obtain this research data by means of interviews, observation and documentation. Some of them said it was a way to balance their profession and responsibilities at home. Prioritize what is more important, create daily activities to manage time so that time for work and family is balanced. The strategy used by career women to overcome challenges in parenting in the digital era is by implementing a consistent positive daily routine. Career women in the digital era have a dual role, namely as housewives and professionals outside the home. This can create challenges in parenting, such as: Lack of time with children, Difficulty in instilling positive values, However, career women can overcome these challenges with various strategies and are able to balance them.